2004
DOI: 10.1093/humrep/deh375
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stimulation by concomitant administration of cetrorelix acetate and HMG following Diane-35 pre-treatment for patients with polycystic ovary syndrome: a prospective randomized study

Abstract: The Diane/cetrorelix protocol has a similar pregnancy outcome to the GnRH agonist long protocol for women with PCOS undergoing IVF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 33 publications
13
55
0
Order By: Relevance
“…One of them was found in a patient with twin pregnancy and one in a patient with triplet pregnancy. Similar occurrence of ovarian hyperstimulation syndrome in both studied groups was reported by Bahceci et al (5% vs. 7.1%) [38] and Hwang et al (8% vs. 8.3%) [39]. On the contrary, Ashrafi et al [37] reported significantly higher number of PCOS patients at risk of developing OHSS (more than 20 follicles visited in each ovary or E 2 >3,000 pg/ml) in patients in GnRH antagonist arm than GnRH agonist arm of the study (0% vs. 30.4%, p=0.004)…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…One of them was found in a patient with twin pregnancy and one in a patient with triplet pregnancy. Similar occurrence of ovarian hyperstimulation syndrome in both studied groups was reported by Bahceci et al (5% vs. 7.1%) [38] and Hwang et al (8% vs. 8.3%) [39]. On the contrary, Ashrafi et al [37] reported significantly higher number of PCOS patients at risk of developing OHSS (more than 20 follicles visited in each ovary or E 2 >3,000 pg/ml) in patients in GnRH antagonist arm than GnRH agonist arm of the study (0% vs. 30.4%, p=0.004)…”
Section: Discussionsupporting
confidence: 89%
“…However, LH level in patients prepared for COH is already decreased with oral contraceptive (OC) on the preceding cycle [39]. Subsequently, according to our results, pulsative LH secretion in GnRH antagonist protocol within the normal physiological range did not have effect on overall outcome.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Research for alternative GnRH antagonist protocols regarding the timing of its initiation has shifted towards earlier antagonist initiation than Day 6 of stimulation (Elkind-Hirsch et al, 2003;Kolibianakis et al, 2003a;Hwang et al, 2004;Lainas et al, 2005). Support for earlier antagonist initiation was further provided by observations that the exposure to LH and E 2 in the early follicular phase of a GnRH antagonist cycle was negatively associated with the probability of pregnancy (Kolibianakis et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%